Sarah Locke with family. - Unknown:::Creator::::::::::::
Sarah Anne Jane Locke as a child posing with her father, mother and brother. Another unidentified couple with their four children are also in the portrait. Sarah Locke is standing behind her father and mother on the left hand side.